FUNDAMENTALS OF MANAGEMENT OF INCLUSIVE DEVELOPMENT OF BUSINESS STRUCTURES OF AGRIBUSINESS - KUSHNIR, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Entrepreneurship plays a vital role in the development of agriculture. Its development in agricultural production requires a balanced approach to implementing agricultural and food policy. It is emphasized that an essential component of managing the inclusive development of agribusiness entrepreneurial structures is the control over implementing an investment business project in the inclusive sphere of activity. The need to establish an inefficient management method in months of a significant decrease in profitability was emphasized. The structure of socioeconomic standards for checking the methods of managing the inclusive development of enterprises on the example of an agricultural firm is considered. Management of the inclusive development of entrepreneurial structures of agribusiness involves the implementation of evaluation, restoration, and increase of its pace. The evaluation takes place with the help of the indicator of inclusive development and the restoration and increase of development rates - with the help of management technology by goals and a bank of methods and techniques for adjusting methods of managing agribusiness business structures. The scheme of using business methods and techniques for adjusting the methods of managing the inclusive development of enterprises is detailed. Examples of the restoration of inclusive development by the rings of the chain of adding consumer properties to the product and the components of the complex activity of the entrepreneurial structure of agribusiness are considered. The practical difficulties that today accompany the development of an inclusive model of economic growth in agribusiness are analyzed. It is proven that the management of an enterprise or business is more concrete and is explained as a purposeful management of all divisions and links of the enterprise for organization and coordination. The theoretical basis of the above provisions is the mechanism of transferring entrepreneurial structures of agribusiness to the state of inclusive development, which, unlike the existing one, is based on the coordination of the market signal (about the vector of the leading consumer property of the product) with a particular trajectory (attractor) of the inclusive development of the business entity.
Keywords: management; inclusive development; decision-making; agribusiness